Tripled likelihood: polypharmacy increases the occurrence of drug therapy problems in hospitalized pediatric patients - Takele, Bereket; Koyra, Hailu Chare; Sidamo, Temesgen; Lerango, Temesgen Leka (Frontiers in Pharmacology, 2024)
Background: A drug therapy problem (DTP) is any undesirable event experienced by a patient that accompanies drug therapy, prevents the patient from achieving their desired therapeutic goals, and requires expert judgment to resolve. Pediatric populations are at a higher risk of DTP than adults due to their immature organ systems, including the liver and kidneys, which play crucial roles in drug metabolism and excretion. Most previous studies have focused on only one element of DTP. Therefore, by considering all elements of DTP, we aimed to assess the prevalence of DTP and associated factors among pediatric patients admitted to the Wolaita Sodo University Comprehensive Specialized Hospital.Methods: An institution-based cross-sectional study was conducted among pediatric patients admitted to Wolaita Sodo University Comprehensive Specialized Hospital from July 8, 2020, to July 7, 2021. A simple random sampling technique was employed to select study participants. Cipolle's and Strand's classification method of drug therapy problems was used to identify and categorize DTP. Data were obtained by reviewing the patient's medical records using a data abstraction checklist, entered into Epi data version 4.6, and exported to SPSS version 25 for analysis. Binary logistic regression analysis was performed to identify independent predictors of DTP.Results: Medical records of 369 pediatric patients were reviewed, and the overall prevalence of DTP was 60.2% (95% CI:55.2%, 65.2%) with a total of 281 identified DTPs. Among them, 164 (74.2%) had only one DTP. Need additional drug therapy was the most common (140 [49.8%]) DTP identified. The number of disease conditions (AOR = 2.13, 95% CI:1.16, 3.92), polypharmacy (AOR = 3.01, 95% CI:1.70, 5.32), and duration of hospital stay (AOR = 1.80, 95% CI:1.04, 3.10) were independent predictors of DTP among admitted pediatric patients.The prevalence of DTP in pediatric patients in the current setting was high. The number of disease conditions, polypharmacy, and duration of hospital stay were independent predictors of DTP. Enhancements to pharmaceutical care services, optimized dosage practices, improved deprescribing by clinicians, and efficient, comprehensive diagnostic procedures have the potential to significantly reduce specific drug therapy problems in hospitalized pediatrics.